Celiac disease and obstetric complications: a systematic review and metaanalysis - Saccone, Gabriele; Berghella, Vincenzo; Sarno, Laura; Maruotti, Giuseppe M.; Cetin, Irene; Greco, Luigi; Khashan, Ali S.; McCarthy, Fergus; Martinelli, Domenico; Fortunato, Francesca; Martinelli, Pasquale (American journal of obstetrics and gynecology, 2016)
The aim of this metaanalysis was to evaluate the risk of the development of obstetric complications in women with celiac disease. We searched electronic databases from their inception until February 2015. We included all cohort studies that reported the incidence of obstetric complications in women with celiac disease compared with women without celiac disease (ie, control group). Studies without a control group and case-control studies were excluded. The primary outcome was defined a priori and was the incidence of a composite of obstetric complications that included intrauterine growth restriction, small for gestational age, low birthweight, preeclampsia and preterm birth. Secondary outcomes included the incidence of preterm birth, intrauterine growth restriction, stillbirth, preeclampsia, small for gestational age, and low birthweight. The review was registered with PROSPERO (CRD42015017263) before data extraction. All authors were contacted to obtain the original databases and perform individual participant data metaanalysis. Primary and secondary outcomes were assessed in the aggregate data analysis and in the individual participant data metaanalysis. We included 10 cohort studies (4,844,555 women) in this metaanalysis. Four authors provided the entire databases for the individual participant data analysis. Because none of the included studies stratified data for the primary outcome (ie, composite outcome), the assessment of this outcome for the aggregate analysis was not feasible. Aggregate data analysis showed that, compared with women in the control group, women with celiac disease (both treated and untreated) had a significantly higher risk of the development of preterm birth (adjusted odds ratio, 1.35; 95% confidence interval, 1.09–1.66), intrauterine growth restriction (odds ratio, 2.48; 95% confidence interval, 1.32–4.67), stillbirth (odds ratio, 4.84; 95% confidence interval, 1.08–21.75), low birthweight (odds ratio, 1.63; 95% confidence interval, 1.06–2.51), and small for gestational age (odds ratio, 4.52; 95% confidence interval, 1.02–20.08); no statistically significant difference was found in the incidence of preeclampsia (odds ratio, 2.45; 95% confidence interval, 0.90–6.70). The risk of preterm birth was still significantly higher both in the subgroup analysis of only women with diagnosed and treated celiac disease (odds ratio, 1.26; 95% confidence interval, 1.06–1.48) and in the subgroup analysis of only women with undiagnosed and untreated celiac disease (odds ratio, 2.50; 95% confidence interval; 1.06–5.87). Women with diagnosed and treated celiac disease had a significantly lower risk of the development of preterm birth, compared with undiagnosed and untreated celiac disease (odds ratio, 0.80; 95% confidence interval, 0.64–0.99). The individual participant data metaanalysis showed that women with celiac disease had a significantly higher risk of composite obstetric complications compared with control subjects (odds ratio, 1.51; 95% confidence interval, 1.17–1.94). Our individual participant data concurs with the aggregate analysis for all the secondary outcomes. In summary, women with celiac disease had a significantly higher risk of the development of obstetric complications that included preterm birth, intrauterine growth restriction, stillbirth, low birthweight, and small for gestational age. Since the treatment with gluten-free diet leads to a significant decrease of preterm delivery, physicians should warn these women about the importance of a strict diet to improve obstetric outcomes. Future studies calculating cost-effectiveness of screening for celiac disease during pregnancy, which could be easily performed, economically and noninvasively, are needed. In addition, further studies are required to determine whether women with adverse pregnancy outcomes should be screened for celiac disease, particularly in countries where the prevalence is high.